46 ELECTRO-CATHETER EXTRACTION IN JUGULAR ACCESS:METHODS AND TECHNIQUES. (15th December 2022) - Marzuolo, Cinzia
Abstract: A significant increase of Pacemaker implantation has resulted in an increase in the number of extractions due to the onset of infections and malfunctions. The transvenous leads extraction by means of a dilator sheath can be difficult for possible fibrotic or calcified adhesions and vegetations along the path of the leads. In 90% of cases the firm adhesions are in the superior vena cava-right atrium, of the tricuspid valve ring of the papillary muscles of the right ventricle and in the lead insertion zone. If standard extraction from the implantation site is difficult along the axis subclavian venous-anonymous vena-superior vena cava, due to the presence of tenacious adhesions along the course of the leads, it is necessary to resort to a right internal jugular approach. During the standard extraction there are particularly delicate points like the anonymous trunk and superior vena cava. At this point the sheath is perpendicular to the vein and there is the possibility of vascular injury. Moreover, the twisting of the sheath doesn't permit a favorable approach at the second part of the lead. In fact, it is very difficult that the force applied during the rotation of the sheaths arrives at the tip of the sheath and is not sufficient to win against the adherences. In this case a right internal jugular approach becomes necessary. This method facilitates the lead extraction because the position of the jugular vein is rectilinear with the superior vein cava and the right part of the heart which permits a better and more precise alignment of the sheath with the vein and hearth cavity. The sheath-lead system has a parallel progress at anonymous vein, the superior vein cava and right atrium. This method reduces vascular injury and makes sheath rotation movement more efficient for resection of adherence, furthermore, for large vegetations it is possible to use big sheaths to simplify the resection. The jugular approach involves the introduction from the femoral vein of a pig tale or a deflectable catheter to take the lead into the right atrium making it intravascular. Furthermore, we proceed with the canalization of the jugular vein in sterile method. Then position an introductory 11 Fr by which a lasso catheter will be introduced. The objective is to capture the lead and bring it out of the jugular vein. Then, the operator will apply the sheath-catheter system and given the good position will proceed with the extraction of the lead, by using rotating movements. The entire procedure is done with a fluoroscopy guide with the use of septums to define the field of view only of area of interest and the exposure of the operators. During the important steps such as the capture of the lead by lasso, the use of ad hoc projections, that help the operator in capturing images, is essential to have a clear reference of the position within the atrium of the catheter itself. During the entire procedure, the modulation of the radiant dose is very important, in fact a Low Dose approach can be chosen at first while doses are increased when needed. Radiation protection in these procedures, which can be challenging from a fluoroscopic point of view, is essential. The success of the procedure is the result of skills and experience of all operators engaged: doctors, nurses, and radiology technicians. Figure 1 Use of pigtail to capture the catheter (left); catheter lasso (center); sheath extraction (right)